Structural and Optical Properties of Fluorine Doped Tin Oxide Thin Film Deposited by Home Built Spray Pyrolysis Unit - Koirala, Maha Prasad; Joshi, Leela Pradhan (Himalayan Physics, 2017)
Fluorine doped Tin Oxide (FTO) thin films were deposited on glass substrates by home built spray pyrolysis setup at (400 ± 5)ºC. The method was found to be very economic and functional. The deposited FTO films were highly transparent and had low resistivity. The structural investigation of as-prepared films was performed using X-ray diffraction. Our results showed that a deposited FTO film was of polycrystalline nature with preferential orientation along (211) planes. The direct band gap value was found to be 3.25eV for 10% FTO film. The sheet resistance of this film was measured to be 68 Ω/ square. The effect of fluorine doping concentration on its band gap was also studied in this report. The Himalayan Physics Vol. 6 & 7, April 2017 (58-60)